ANALISIS MEMBACA PEMAHAMAN PADA SISWA KELAS V DI SD ISLAM AL-ABROR KECAMATAN SITUBONDO KABUPATEN SITUBONDO - Imam Taufik; Nur Holifatuz Zahro (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2018)
Reading comprehension is a process of digging or understand the information of the reading where the reader read material by capturing the basic thoughts sharper and deep, so you feel there is a certain satisfaction after the reading material was read to completion. This study aimed to describe about reading comprehension in grade V in SD Islam Al-Abror. This study uses a descriptive qualitative research approach with samples of the study were all students of class V, amounting to 22 students. The procedure of collecting data in this study using four methods namely observation, interview, documentation and Reading Comprehension Test. Analysis of the data used is interactive analysis using Data Reduction, Data Presentation, Withdrawal and Withdrawal Conclusion. Based on the research that has been conducted, the results showed that the students of class V SD Islam Al-Abror been able to understand the contents of the texts have been read, but every student in the class V SD Islam Al-Abror certainly different levels of understanding. Of the 22 students, 14 or 64% is students with reading comprehension level infransial, then 4 or 18% of students in reading comprehension level literal as well as four other people or 18% of the students with reading comprehension level of critical or critical. On the literal level of understanding of all students in grade V SD Islam Al-Abror able to answer all the test and interview well, so we can say the entire fifth grade students of SD Islam Al-Abror is a student with a literal reading comprehension level is good. Then, at the level of reading comprehension infransial almost all students were able to answer all the test well, but 4 students can not answer properly, so that four students are located at the literal level of understanding only. At a critical understanding there are only four people who can answer questions well, while others have not been able to answer well to be in the level of understanding infransial